Resisting Concepts as Starting Points in a High School Leadership Pathway Alongside Indigenous Youth (LEARNing Landscapes, 2023)
This writing draws on an ongoing narrative inquiry with 10 Indigenous youth as they negotiated their lives within a high school leadership pathway. Our research demonstrates the need to resist starting in concepts as an intentional shift to being and becoming wakeful to storied lives on and off school landscapes. Three resonant threads are highlighted as we listened across the youths’ lives. These threads are framed as pathways the youth asked us to consider in terms of reimagining schools as places of unfolding kinship, reimagining schools beyond notions of becoming responsible adults, and reimagining in-between spaces as landscapes that matter.
Keywords: Indigenous youth; high school; after-school; leadership; narrative inquiry